DONGKARI: INTERPRETASI PENEMBANG TERHADAP PEMBENTUKAN ORNAMENTASI VOKAL TEMBANG SUNDA CIANJURAN - Denis Setiaji (Institut Seni Indonesia Surakarta, 2020)
The following research aims to explain about how Dongkari as aesthetic concept, constructing ornamentation in Tembang Sunda Cianjuran. This research employs phenomenology approach also filedwork activity and depth interview with singer or “penembang” who exist around Bandung, West Java. This studydescribes the Dongkari as element of ornamentation which is used by penembang to create ornamentation in performing Tembang Sunda Cianjuran songs. As a result, Dongkari as the basic construction of ornamentation, should be operated by penembang based on virtuocity and interpretation of each penembang.